(untitled) (Comprehensive Journal of Science, 2026)
This research aimed to identify the obstacles facing kindergarten teachers in Zawiya city in implementing storytelling activities, given the story’s vital role in a child’s cognitive and emotional development and the observed gap between theory and practice. Adopting a descriptive-analytical approach, the study utilized a sample of (30) teachers. Data were collected using an obstacles assessment questionnaire and analyzed using arithmetic means and standard deviations. The results revealed high-level challenges, primarily structural constraints such as inadequate facilities and classroom overcrowding, administrative obstacles including a lack of support, as well as challenges related to the digital age, specifically the distraction caused by electronic devices and the teachers’ reliance on traditional narration methods. Consequently, the research recommended improving the classroom environment, training teachers on modern and digital storytelling techniques, and providing supportive procedural guides.